Defining High‐risk Emergency Chief Complaints: Data‐driven Triage for Low‐ and Middle‐income Countries. (18th June 2020) - Rice, Brian; Leanza, Joseph; Mowafi, Hani; Thadeus Kamara, Nicholas; Mugema Mulogo, Edgar; Bisanzo, Mark; Nikam, Kian; Kizza, Hilary; Newberry, Jennifer A.; Strehlow, Matthew; ,; Kohn, Michael
Abstract: Objectives: Emergency medicine in low‐ and middle‐income countries (LMICs) is hindered by lack of research into patient outcomes. Chief complaints (CCs) are fundamental to emergency care but have only recently been uniquely codified for an LMIC setting in Uganda. It is not known whether CCs independently predict emergency unit patient outcomes. Methods: Patient data collected in a Ugandan emergency unit between 2009 and 2018 were randomized into validation and derivation data sets. A recursive partitioning algorithm stratified CCs by 3‐day mortality risk in each group. The process was repeated in 10, 000 bootstrap samples to create an averaged risk ranking. Based on this ranking, CCs were categorized as "high‐risk" (>2× baseline mortality), "medium‐risk" (between 2 and 0.5× baseline mortality), and "low‐risk" (<0.5× baseline mortality). Risk categories were then included in a logistic regression model to determine if CCs independently predicted 3‐day mortality. Results: Overall, the derivation data set included 21, 953 individuals with 7, 313 in the validation data set. In total, 43 complaints were categorized, and 12 CCs were identified as high‐risk. When controlled for triage data including age, sex, HIV status, vital signs, level of consciousness, and number of complaints, high‐risk CCs significantly increased 3‐day mortality odds ratio (OR = 2.39, 95% confidence interval [CI] = 1.95 to 2.93, p < 0.001) while low‐risk CCs significantly decreased 3‐day mortality odds (OR = 0.16, 95% CI = 0.09 to 0.29, p < 0.001). Conclusions: High‐risk CCs were identified and found to predict increased 3‐day mortality independent of vital signs and other data available at triage. This list can be used to expand local triage systems and inform emergency training programs. The methodology can be reproduced in other LMIC settings to reflect their local disease patterns.